HUBUNGAN PENERAPAN KAWASAN TANPA ROKOK (KTR) DENGAN PERILAKU MEROKOK KELUARGA PASIEN DI RUMAH SAKIT UMUM DELIA KABUPATEN LANGKAT - Andini Mentari Tarigan; Muhammad Firza Syahlefi Lubis; Dyna Safitri Rakhelmi Rangkuti (Jurnal Mutiara Kesehatan Masyarakat, 2022)
Smoking behavior is a behavior that burns one of the tobacco products that is intended to be burned, smoked and/or inhaled. In Indonesia, smoking is considered a very normal habit. Smoking behavior never subsides because it is a behavior that can still be tolerated by the community. The application of KTR allows the community to be able to enjoy clean and healthy air and avoid various risks that are detrimental to health and life. Based on the initial survey conducted by the researcher, the results obtained, from 2 respondents, 1 respondent did not know what it was called a no-smoking area (KTR), so he smoked in the hospital environment and 1 respondent said he could not resist the urge to smoke so he smoked. in the hospital environment. Smoking habits in the hospital environment may be caused by a lack of warning from the health workers who work at the delia general hospital, Langkat district so that visitors who come to the hospital do not care about the existence of KTR even though the hospital has implemented the Non-Smoking Area (KTR). ). The purpose of this study was to determine the relationship between the application of a non-smoking area (KTR) and the smoking behavior of the patient's family at RSU Delia, Langkat Regency in 2020. This research is an explanatory research, which is a type of research aimed at explaining the phenomenon of research problems and explaining the relationship between variables independent with the dependent variable which is intended to determine the relationship between the application of a non-smoking area (KTR) with smoking behavior in the patient's family at RSU Delia, Langkat Regency. The population in this study was the patient's family who visited Delia RSU as many as 45 people to see the smoking behavior of the patient's family at Delia RSU, Langkat Regency